ON A NEW NEMATODE METAQUIMPERIA CHAUHANI N. Sp. FROM FRESH WATER FISH BAGARIUS BAGARIUS (HAM.) - MISRA, R. P.; KUMARTIWAR, SUNIL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
Metaquimperia chauhan in sp. has been described from the intestine of fresh water fish Bagarius bagarius (Ham) at Lucknow. It is distinguished from other species by caudal papillae (4 pairs preanal and 5 pairs postanal), small gubernaculum and absence of anal papillae.